Teaching experience and multicultural voice: Steps and words in the life history of an afrodescendant teacher - Cañón Flórez, Lilia; Monroy González, Myriam Esperanza; Salcedo Casallas, Javier Ricardo (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article proposes the establishment of multicultural relationships in school settings, particularly with afrodescendant teachers. To this purpose, we suggested the use of emerging and unifying concepts of subjectivity, multiculturalism, territory, and pedagogical experience along with the educational strength of life history in a dialogic relationship with the students. The objective of this study is to explore the daily life and interaction between students and teachers by means of the life history approach, in order to make visible the framework where knowledge and school practices constitute subjectivities. This perspective sets comprehension as a possibility for transformation rooted in interpretation and dialogue with the meanings and senses expressed by others through words and silences. Therefore, this work generates several narratives of an Afro-Colombian teacher at Ciudadela Educativa de Bosa High School, whose ontology and epistemology represents both the practice and the concept of teaching experience, and makes possible the emergence of new afro-urban ethnicities, which fortify multicultural relations.